LEGAL LIABILITY OF PROPERTY DEVELOPERS REGARDING THE FULFILLMENT OF OBLIGATIONS TO CONSUMERS IN SALE AND PURCHASE TRANSACTIONS USING THE BINDING SALE AND PURCHASE AGREEMENT - Ratna, Yulvita; Djajaputra, Gunawan (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
Business people show great interest in the development of the property industry. With promising market prospects, developers have significant legal responsibilities to potential buyers. To ensure legal certainty and avoid future conflicts, consumers must understand and comply with the legal rules contained in the agreement. The Sales and Purchase Agreement functions as a contract between the seller and the buyer at the initial stage of the home buying and selling process. This research examines the developer's responsibility towards consumers in house sale and purchase agreements through the Agreement of Sale and Purchase Binding mechanism, because a lack of consumer awareness and knowledge can increase risks to their rights. The method used in this research is based on normative juridical. The aim of this research is to determine the developer's legal responsibility towards buyers as consumers, so that there is legal certainty for buyers using the Agreement of Sale and Purchase Binding system. Developers must bear the losses experienced by consumers in accordance with Article 19 of Law Number 8 of 1999 concerning Consumer Protection. In accordance with Article 19 of Law Number 8 of 1999 concerning Consumer Protection, this research aims to determine the developer's legal responsibility towards buyers as consumers, so that buyers can obtain legal certainty through the Agreement of Sale and Purchase Binding system. In addition, the developer is responsible for providing accurate information and guaranteeing the quality of construction, which includes the construction period to the maintenance period, until all sales and purchase agreements are completed.